Letramento Crítico em tempos de fake news: investigação dos desafios e percepções em uma prática pedagógica de língua inglesa - Oliveira, Alessandra Rosa de (2020)
The objective of this work was to investigate the extent to which a didactic proposal for teaching English in a critical literacy perspective (MONTE MÓR, 2013; SOUZA, 2011; STREET, 2014) contributed to develop a critical reading of fake news in a public school in Uberlandia City, State of Minas Gerais. The current proliferation of fake news and its interference in decision-making that affects thousands of people (D'ANCONA, 2018; DAVIES, 2016; DUNKER, 2017; JONES, 2019; TIBURI; 2017) justify the importance, in language teaching, critical reading understood as “critique” (MONTE MÓR, 2013), in order to benefit students' access to a diversity of points of view in the process of forming opinions, in a complex, plural and heterogeneous world. In addition to theories on critical literacy, another theoretical contribution to the reflections on fake news and criticality were the philosophical discussions about truth and lies (ARENDT, 2014; BAUMAN, 1998; DELEUZE, 1976; NIETZSCHE, 2008). The research took place in an elementary school with 9th grade students in two classes which I am the English teacher. The chosen methodology was the qualitative-interpretative paradigm precisely because it provides a critical reflection on the research and the influences of the researcher in the researched environment and in the results (de GRANDE, 2011). Initial and final questionnaires, semi-structured interviews, and field notes were applied over the six weeks in which the didactic sequence was applied. I conclude, at the end of the work, that it was relevant to address the fake news subject in the classroom, in the sense of having contributed to the construction of the students' criticality. It remains to be seen, however, whether the work developed over six weeks was sufficient to promote significant changes in the way students read news, which seems to reflect an autonomous literacy model, towards an ideological model (STREET, 2014).